The impact of non-profit temping agencies on individual labour market success in the West German state of Rhineland-Palatinate - Michael Lechner; Friedhelm Pfeiffer; Hannes Spengler; Matthias Almus (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2000)
The paper presents an econometric evaluation of the effects of subsidised non-profit temporary employment agencies - a programme of the West German active labour market policy - on individual labour market outcomes. The empirical analysis is based on individual data from files for computer-assisted job brokering in Rhineland-Palatinate. Econometric estimates based on matching methods suggest that the programme generated a statistically significant additional reintegration success of about 13 per centage points. Furthermore within the first four month after leaving the programme, the estimated effect was about half a month additional employment for the participants.
Keywords: J64; C52; J68; 330; Econometric evaluation methods; matching; active labour market policies; temporary employment agencies; Arbeitsvermittlung; Leiharbeit; Rheinland-Pfalz